2010
DOI: 10.1051/0004-6361/200811114
|View full text |Cite
|
Sign up to set email alerts
|

Quark-nova remnants

Abstract: XTE J1810−197 and 1E 1547.0−5408 are two transient anomalous X-rays pulsars (AXPs) exhibiting radio emission with unusual properties. In addition, their spin down rates during outburst show opposite trends, which so far has no explanation. Here, we extend our quark-nova model for AXPs to include transient AXPs, in which the outbursts are caused by transient accretion events from a Keplerian (iron-rich) degenerate ring. For a ring with inner and outer radii of 23.5 km and 26.5 km, respectively, our model gives … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Dissipation of magnetic bubbles generated at the ring during these outburst provides a source of transient radio emission which has been associated with some AXPs following bursting periods. 13 When these accretion events happen the inner ring of the disk will be heated by radiation from the surface of the quark star. During quiescent phases, the quark star-ring system should have two emission spectra (X-ray and black body).…”
Section: Keplerian Debris: Axpsmentioning
confidence: 99%
“…Dissipation of magnetic bubbles generated at the ring during these outburst provides a source of transient radio emission which has been associated with some AXPs following bursting periods. 13 When these accretion events happen the inner ring of the disk will be heated by radiation from the surface of the quark star. During quiescent phases, the quark star-ring system should have two emission spectra (X-ray and black body).…”
Section: Keplerian Debris: Axpsmentioning
confidence: 99%
“…As a last application, we consider the formation of a SQS from a pure metastable NS, which might occur once and if an initial seed of SQM has been formed in one of several hypothetical ways [11,88,89,90], for example in a two-step phase transition of nuclear matter to 2QM to SQM [91,92], or in the combustion of hot nuclear matter [93,94,95,96,97,98]. This transition is accompanied by a huge energy release, which could be associated with the long gammaray bursts [99,100,101] or the two-neutrino-burst scenario supernovas [102].…”
Section: Conversion Of Neutron Stars Into Strange Quark Starsmentioning
confidence: 99%
“…2). Follow‐up studies of neutrino and photon emission processes during the QN (Vogt, Rapp & Ouyed 2004; Ouyed et al 2009b) have shown that these outermost layers (10 −4 to 10 −3 M ⊙ ) can be ejected with up to 10 53 erg in kinetic energy. Nucleosynthesis simulations of the evolution of the neutron‐rich QNE was found to produce primarily heavy elements with mass number, A > 130 (Jaikumar et al 2007).…”
Section: Quark Nova Modelmentioning
confidence: 99%